APLIKASI SLIDING MODE CONTROL (SMC) UNTUK MEREDUKSI OSILASI TEGANGAN KELUARAN BOOST CONVERTER PADA PANEL SURYA - Aldi Lutfil Hikam; n/a Wijono; Tri Nurwati (Jurnal Mahasiswa TEUB, 2021)
Abstrak Tegangan yang dihasilkan sel surya tergantung kondisi intensitas cahaya matahari di sepanjang waktu. Sehingga dibutuhkan metode untuk melacak titik daya maksimum sel surya yang berubah menggunakan Maximum Power Point Tracker (MPPT). Untuk mengendalikan tegangan sel surya maka digunakan konverter, jenis konverter yang digunakan adalah Boost Converter yang mengubah tegangan keluaran sel surya menjadi lebih besar. Namun tegangan keluaran yang dihasilkan oleh Boost Converter memiliki kekurangan seperti adanya osilasi. Untuk mengatasi hal tersebut, dibutuhkan pengendali pada Boost Converter. Pengendali yang diterapkan pada skripsi ini adalah Sliding Mode Control (SMC). Dimana masukan dari Boost Converter adalah keluaran dari sel surya yang bervariasi tergantung pada perubahan iradiasi cahaya matahari. Penelitian dilakukan dengan simulasi pada MATLAB Simulink yang disimulasikan pada sistem open loop dan close loop. Berdasarkan analisa penelitian tegangan keluaran pengendali SMC dapat mempercepat settling time tegangan keluaran dari nilai settling time open loop. Pada saat terjadi perubahan iradiasi pada waktu tertentu yang menyebabkan terjadinya lonjakan tegangan, pengendali SMC dapat memperbaiki tegangan recovery time lebih cepat dari sistem open loop. Ketika beban R bervariasi tegangan yang dihasilkan sel surya dan tegangan keluaran boost converter semakin besar seiring dengan bertambahnya beban R. Settling time ketika beban R berubah pengendali SMC mempunyai settling time yang lebih cepat dari settling time Open Loop. Kata Kunci— Sel Photovoltaic, MPPT, Boost Converter, Sliding Mode Control (SMC), settling time, recovery time. Abstract The voltage generated by solar cells depends on the conditions of the sun's light intensity at all times, so a method is needed to track the maximum power point of a changing solar cell using the Maximum Power Point Tracker (MPPT). To control the voltage of solar cells, using the converter. The type of converter used is the Boost Converter, which changes the solar cells' output voltage to a bigger one. However, the output voltage generated by the Boost Converter has disadvantages such as oscillations. Need A controller on the Boost Converter to overcome this. The controller applied in this thesis is Sliding Mode Control (SMC). The Boost Converter's input is the output of solar cells, which varies depending on changes in sunlight irradiation. They researched by simulating the MATLAB Simulink simulated on open loop and close loop systems. Based on the research analysis, the SMC controller's output voltage can accelerate the settling time of the output voltage from the open-loop settling time value. When there is a change in irradiation at a specific time that causes a voltage spike, the SMC controller can improve the voltage recovery time faster than the open-loop system. When the load R varies, the voltage generated by the solar cell and the boost converter's output voltage increases with the increase in R load. When the load R changes, the SMC controller has a settling time that is faster than the Open Loop settling time. Based on the research analysis, the SMC controller's output voltage can accelerate the settling time of the output voltage from the open-loop settling time value. When there is a change in irradiation at a specific time that causes a voltage spike, the SMC controller can improve the voltage recovery time faster than the open-loop system. When the load R varies, the voltage generated by the solar cell and the boost converter's output voltage increases with the increase in R load. When the load R changes, the SMC controller has a settling time that is faster than the Open Loop settling time. Keywords— Photovoltaic Cells, MPPT, Boost Converter, Sliding Mode Control (SMC), settling time, recovery time.